2020
DOI: 10.3390/molecules25153539
|View full text |Cite
|
Sign up to set email alerts
|

Dissolving Cellulose in 1,2,3-Triazolium- and Imidazolium-Based Ionic Liquids with Aromatic Anions

Abstract: We present 1,2,3-triazolium- and imidazolium-based ionic liquids (ILs) with aromatic anions as a new class of cellulose solvents. The two anions in our study, benzoate and salicylate, possess a lower basicity when compared to acetate and therefore should lead to a lower amount of N-heterocyclic carbenes (NHCs) in the ILs. We characterize their physicochemical properties and find that all of them are liquids at room temperature. By applying force field molecular dynamics (MD) simulations, we investigate the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 71 publications
4
42
0
Order By: Relevance
“…Based on the specific physicochemical features described elsewhere for EMIMCl- and EMIMCl·AcOH-based mixtures [ 28 ], their solvent properties should also be different. There are many papers on dissolving cellulose in the ionic liquid 1-ethyl-3-methylimidazolium acetate (EMIMOAc), which is a very good cellulose solvent (>20 wt% at 80 °C) [ 29 , 30 ]. Moreover, it is well known EMIMCl is an excellent solvent for cellulose [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the specific physicochemical features described elsewhere for EMIMCl- and EMIMCl·AcOH-based mixtures [ 28 ], their solvent properties should also be different. There are many papers on dissolving cellulose in the ionic liquid 1-ethyl-3-methylimidazolium acetate (EMIMOAc), which is a very good cellulose solvent (>20 wt% at 80 °C) [ 29 , 30 ]. Moreover, it is well known EMIMCl is an excellent solvent for cellulose [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with recent work by Brehm et al, who reported that the cellulose−anion interactions are significantly stronger than cellulose−cation interactions in ILs, and hence, the former contribute much more significantly to the total potential energy of cellulose dissolution. 54 Thus, ILs with common anions are expected to display very similar macroscopic solution properties, when cellulose is dissolved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This suggests that there may be more significant differences observable between EmimAc and BmimAc when cellulose with a larger DP is dissolved. While cellulose−anion interactions are expected to be more important than cellulose−cation interactions in ILs, 54 possibly the contribution of the cation may become more significant in BmimAc compared to EmimAc. [η] is more comparable between V-cell/BmimAc and α-cellulose/BmimCl solutions, which have the same cation, suggesting that cellulose−cation interactions may be more important for dissolution of larger DP cellulose.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1,[4][5][6] Considering that cellulose presents a complex structure as well as a high degree of polymerization (DP), the dissolution process is considered a critical step for its valorisation due to its insolubility in water and most conventional organic solvents. 3,4,6,7 Nowadays, different existing technologies for dissolution and processing of cellulose are applied at industrial scale, however aggressive solvents, or processes, which present a threat to the environment, are used 6,8 namely "viscose process", which consists in the chemical functionalization of cellulose through its hydroxyl groups with carbon disulphide to produce xanthate esters 5,9 and "Lyocell process", which uses aqueous N-methylmorpholine-Noxide (NMNO) as solvent. 5,9,10 Recently, Xu et al 8 reported others examples of solvents or mixtures of solvents investigated for cellulose dissolution processes, such as aqueous cuprammonium or cupriethylenediamine hydroxide as aqueous non-derivatizing solvents, 11 DMSO/tetrabutylammonium uoride (DMSO/TBAF) as non-aqueous non-derivatizing solvents, 11 N,N-dimethylformamide/ N 2 O 4 (DMF/N 2 O 4 ) as aprotic derivatizing solvents, 11 LiCl/N,Ndimethylacetamide (LiCl/DMA) solvent, 12 LiClO 4 $3H 2 O, 13 LiCl/ dimethyl sulfoxide (LiCl/DMSO) solvent, 14 aqueous NaOH combined with urea 15 or thiourea 16 solvents, dimethyl sulfoxide/1,8diazabicyclo- [5.4.0]-undec-7-ene (DMSO/DBU).…”
Section: Introductionmentioning
confidence: 99%